2009
DOI: 10.1088/0022-3727/42/13/135501
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating magnetic field-actuated microvalves for micro- and nanofluidics

Abstract: The feasibility of using tunable magnetic nanoparticles embedded in cylindrical hydrogel materials as a flow regulator via thermo-mechanical gating is studied within microfluidic channels. Ferromagnetic nanoparticles (Fe3O4) encapsulated within a thermo-sensitive polymer network (-poly(N-isopropylacrylamide) (PNIPAM)) was polymerized inside 300 µm diameter micro-capillary tubes. An oscillating magnetic field range 20–125 Oe, (100–1000 kHz) was used to induce heat and control the valving action. Valving action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…We found that the size of the iron particles we used did not negatively affect the valve's function, yet they are considerably more cost efficient than nano-sized beads like the ones used previously. 10 The serpentine micro-channel (width: 0.4 mm and depth: 0.3 mm) was made on a PMMA substrate using a laser cutter (Universal PLS6.75). This serpentine structure helps keeping the PNIPAM in place, and has an increased area efficiency compared to a straight channel.…”
Section: Concept and Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the size of the iron particles we used did not negatively affect the valve's function, yet they are considerably more cost efficient than nano-sized beads like the ones used previously. 10 The serpentine micro-channel (width: 0.4 mm and depth: 0.3 mm) was made on a PMMA substrate using a laser cutter (Universal PLS6.75). This serpentine structure helps keeping the PNIPAM in place, and has an increased area efficiency compared to a straight channel.…”
Section: Concept and Fabricationmentioning
confidence: 99%
“…This serpentine structure helps keeping the PNIPAM in place, and has an increased area efficiency compared to a straight channel. 10 After uniformly distributing 3 mg of the iron micro-particles into the micro-channel, the PMMA substrate was bonded to another PMMA substrate using a thermal-compression bonding system (INSTRON Dual Column Testing Systems). The PNIPAM hydrogel was formed by mixing equal volumes of two different solutions.…”
Section: Concept and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential replacement technologies include electrostatic [10], magnetic [11], torque generated [12], Braille pin [13], thermal [14,15] and shape memory alloy (SMA) [3] actuation.…”
Section: Component-level Developmentsmentioning
confidence: 99%
“…Due to its controlled size, morphology and release, and excellent biocompatibility, biodegradable organic/inorganic micro/nano-particles have been studied extensively [2][3][4][5]. In fact, stimuli-responsive systems could facilitate drug release to reach a target environment.…”
Section: Introductionmentioning
confidence: 99%